2010
DOI: 10.3325/cmj.2010.51.543
|View full text |Cite
|
Sign up to set email alerts
|

Sick Leave and Its Determinants in Professional Soldiers of the Slovenian Armed Forces

Abstract: 543www.cmj.hr Aim To assess whether demographic characteristics, selfrated health status, coping behaviors, satisfaction with important interpersonal relationships, financial situation, and current overall quality of life are determinants of sick leave duration in professional soldiers of the Slovenian Armed Forces.Methods In 2008, 448 military personnel on active duty in the Slovenian Armed Forces were invited to participate in the study and 390 returned the completed questionnaires (response rate 87%). The q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…In our previous studies, we have explored key psychological factors in members of the Slovenian Armed Forces, who reported poorer bio-psycho-social well-being and more burnout, and therefore had reduced working effectiveness and motivation [32]. The determinants of sick leave duration were also researched; longer sick leave duration was found in women soldiers and the respondents were less satisfied with their relationships with coworkers [33]. There are other psychological factors and external triggers, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, we have explored key psychological factors in members of the Slovenian Armed Forces, who reported poorer bio-psycho-social well-being and more burnout, and therefore had reduced working effectiveness and motivation [32]. The determinants of sick leave duration were also researched; longer sick leave duration was found in women soldiers and the respondents were less satisfied with their relationships with coworkers [33]. There are other psychological factors and external triggers, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, another study showed that coping strategies do not affect self-reported sick leave in Slovenian soldiers (26). Since job demands, stress and the coping strategies of the soldiers on missions were not controlled in this study, which is an important limitation, we are not able to speculate about the impact of operational stress on the incidence of anxiety and depression.…”
Section: Discussionmentioning
confidence: 69%
“…Both depression and anxiety are known to be more prevalent in women (37,38), but in our study female gender was not shown to be significantly associated with either the SDS or SAS score (Table 3) or with the co-occurrence of depression and anxiety (Table 4). In one of our previous studies on Slovenian Armed Forces members, longer sick leave duration was found in female soldiers (26) and a negative association between satisfaction with co-workers and female gender was identified (39). It was suggested that special attention should be given to female soldiers when planning supervision, work procedures, and the gender equality policy of the Armed Forces (39).…”
Section: Discussionmentioning
confidence: 99%
“…Self-rated overall health appears to be a valid measure of health status among soldiers (18). Moreover, poorer self-rated health is a significant predictor of longer sick-leave duration (19). Although in the univariate analyses the combat unready soldiers had a statistically higher impact of limitations on everyday activities due to emotional troubles as well as higher intensities of some psychological dimension than the combat ready soldiers, none of the specific psychological dimensions was a significant predictor of soldier combat readiness in multivariate analyses.…”
Section: Discussionmentioning
confidence: 80%